Thermoexpandable Memokath stent: Usage and efficacy in ureteral and urethral strictures in Saudi Arabia - Omar Buksh; Anfar Jar; Ahmad Khogeer; Hani Alzahrani; Rabea Akram; Mohammad Taher; Mahmoud Al Akra'a; Adel Alammari; Islam Junaid (Urology Annals, 2024)
Objectives: Double J (DJ) stent is widely used in cases of ureteric strictures as a temporary solution; however, it has certain limitations, such as the need for frequent exchange. Alternatively, a long-lasting thermoexpandable stent (Memokath™ 051) has been used to relieve ureteral obstructions in comorbid patients with multiple reported advantages, such as longer durability which avoids the need of frequent exchanges. In addition, it can be used in certain cases of urethral strictures. Our study is the first in the region to report the experience and outcome of Memokath stent with ureteral and urethral strictures. Materials and Methods: After local IRB approval, we retrospectively reviewed records of 21 patients who underwent insertion of Memokath 051 stent in the ureter and Memokath 045 in the urethra between 2013 and 2021. Indications of insertion, indwelling duration, and causes of removal were collected and analyzed by SPSS. Results: Twenty-one patients received 21 Memokath stents for 11 ureteral strictures and 10 urethral strictures. Fifty-five percent of ureteral strictures were malignant, and 27.3% of the benign ureteric strictures were transplant ureters. Ureteric memokath stents remained functioning for a mean of 16.1 months. Mean indwelling time for transplant ureteric memokath stents was 24.3 months. Total 4 ureteric stents had migrated, 4 stents blocked, and 2 stents were removed as planned and 1 stent removed due to febrile urinary tract infection (UTI). Ten urethral stents remained in place for mean of 14 months. Three stents were removed as planned with resolution of stricture, two were removed due to blockage, three stents had UTI, one was removed due to pain, and one stent remained functioning until the patient expired. Conclusion: Our outcome is comparable to other published studies, suggesting that ureteric Memokath stent is a better option with adequate indwelling time, especially in transplant ureters, in comparison with DJ stents. In addition, Memokath stents can be used in selected recurrent urethral strictures where surgical reconstruction is not feasible.